2022
DOI: 10.53482/2022_53_402
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying syntax similarity with a polynomial representation of dependency trees

Abstract: We introduce a graph polynomial that distinguishes tree structures to represent dependency grammar and a measure based on the polynomial representation to quantify syntax similarity. The polynomial encodes accurate and comprehensive information about the dependency structure and dependency relations of words in a sentence, which enables in-depth analysis of dependency trees with data analysis tools. We apply the polynomial-based methods to analyze sentences in the ParallelUniversal Dependencies treebanks. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Furthermore, we can also apply the polynomials to other labeled, semi-labeled or unlabeled tree representations of RNA secondary structures. See [15] for an example of a complete polynomial invariant for labeled trees. RNA molecules fold into secondary structures that can be described by paired and unpaired nucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we can also apply the polynomials to other labeled, semi-labeled or unlabeled tree representations of RNA secondary structures. See [15] for an example of a complete polynomial invariant for labeled trees. RNA molecules fold into secondary structures that can be described by paired and unpaired nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…In [13], the author introduced a polynomial that assigns every unlabeled tree a unique polynomial representation; we refer to it as polynomial P . Recent studies have used methods based on polynomial P to analyze the evolution of pathogens [14] and the syntax of languages [15]. Here, we use polynomial P and rooted tree representations to study RNA secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…MDD is used as a new measurement for differentiating human languages. The studies related to MDD are mainly about the decreasing tendency of MDD in human languages which is a universal phenomenon (Futrell et al, 2015;Liu et al, 2016). The quantitative research of dependency distance is mainly related to the study of dependency direction.…”
Section: Dependency Distancementioning
confidence: 99%
“…The sentence is visualized as a hierarchical system with the predicate verb as its root. The dependency distance of a dependency pair is the linear distance between the governor and the dependent (Liu, 2007). See Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Dependency Distance Minimization (DDM) refers to the tendency to shorten the dependency distance in human languages (Ferrer-i-Cancho & Liu, 2014; Liu, 2007; Temperley, 2008). Large-scale cross-linguistic studies have confirmed that DDM is a global property of human languages (Futrell et al, 2015; Liu, 2008; Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%